2011
DOI: 10.1186/1479-5876-9-118
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Transplantation of Adipose-Derived Mesenchymal Stem Cells Markedly Reduced Acute Ischemia-Reperfusion Lung Injury in a Rodent Model

Abstract: BackgroundThis study tested the hypothesis that autologous transplantation of adipose-derived mesenchymal stem cells (ADMSCs) can effectively attenuate acute pulmonary ischemia-reperfusion (IR) injury.MethodsAdult male Sprague-Dawley (SD) rats (n = 24) were equally randomized into group 1 (sham control), group 2 (IR plus culture medium only), and group 3 (IR plus intravenous transplantation of 1.5 × 106 autologous ADMSCs at 1h, 6h, and 24h following IR injury). The duration of ischemia was 30 minutes, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
181
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(223 citation statements)
references
References 38 publications
41
181
0
1
Order By: Relevance
“…Nonetheless, all these changes were significantly reversed by intravenous administration of ADMSCs. Our data are consistent with several recent reports showing that restoration of the levels of some apoptotic markers, such as caspase-3, Bax and Bcl-2, play an essential role in the protective effects of ADMSCs therapy against I/R injury (12,13). Altogether, our findings not only corroborated previous reports that apoptosis produces neuronal death after I/R injury, but also provided evidence that ADMSCs implantation is able to prevent the apoptosis of neurons.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, all these changes were significantly reversed by intravenous administration of ADMSCs. Our data are consistent with several recent reports showing that restoration of the levels of some apoptotic markers, such as caspase-3, Bax and Bcl-2, play an essential role in the protective effects of ADMSCs therapy against I/R injury (12,13). Altogether, our findings not only corroborated previous reports that apoptosis produces neuronal death after I/R injury, but also provided evidence that ADMSCs implantation is able to prevent the apoptosis of neurons.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, adipose-derived MSCs (ADMSCs) have several distinct advantages of being abundant, easy to obtain with minimal invasiveness, and readily cultured to a sufficient number for autologous transplantation without the ethical issues of allografting (10). Recently, a growing body of experimental evidence has demonstrated the effectiveness of ADMSC-based therapy in improving end-organ ischemia or I/R injury (11)(12)(13). However, the possibility that autologous transplantation of ADMSCs may have a neuroprotective effect on cerebral I/R injury has not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, Chen et al 2011, using a model of kidney IR treated using direct injection of ASCs, find increased clearance of creatinine and urea from blood plasma, together with higher levels of the antioxidant markers NAD(P)H quinine oxidoreductase, heme-oxygenase 1/HO-1, glutathione peroxidase, and glutathione reductase [314]. Increased antioxidant marker levels versus controls (i.e., NAD(P)H quinine oxidoreductase and HO-1) have also been reported, together with decreased hepatic oxidative stress upon multiple injections of ASCs in hepatic IR models [312]. In vivo, GFP-labelled ASCs can improve the vasculature in excisional wounds in normal and diabetic rats and are found to coexpress CD31, suggesting their endothelial differentiation [315].…”
Section: Asc-directed Tissue Regeneration: the Role Of Vascularizationmentioning
confidence: 84%
“…Transendocardial injections of ASCs in a minipig model of IR injury results in long-lasting improvements in cardiac function, along with increased angiogenesis and vasculogenesis [311]. Higher numbers of CD31+ve and vWF+ve cells have also been found in models of lung IR following ASC injection, suggesting increased vessel formation [312]. Amelioration of kidney IR injury can be achieved using ASCs [313].…”
Section: Asc-directed Tissue Regeneration: the Role Of Vascularizationmentioning
confidence: 98%
“…Importantly, MSCs express CD59, a complement regulatory protein, and also release complement factor H that protects them from complement lysis (Tu et al 2010;Moll et al 2011). In addition, stimulation through C3aR and C5aR protect MSCs from oxidative damage (Schraufstatter et al 2009) and MSCs produce a number of antioxidants including hemeoxygenase-1 and superoxide dismutase (Kemp et al 2010;Mougiakakos et al 2011), and have been shown to suppress oxidative stress and inflammation in ischemia reperfusion injury models in vivo (Chen et al 2011Sun et al 2011;Du et al 2012). The exact mechanisms of action are unclear; however, MSC protection in these models was associated with increased expression of IL-10, heme oxygenase-1 (HO-1), and hepatocyte growth factor, decreased expression of the proinflammatory cytokines IL-1b, TNF-a, and interferon g (IFN-g), reduced reactive oxygen species, reduced apoptosis and decreased numbers of activated T cells, and infiltrating immune cells (Hara et al 2011;Sun et al 2011;Chen et al 2012;Du et al 2012).…”
Section: Effect Of Mesenchymal Stromal Cells On Ischemia Reperfusion mentioning
confidence: 99%